DISTRIBUSI DAN PENGGUNAAN HABITAT EMPAT SPESIES FELIDAE DI TAMAN NASIONAL BUKIT BARISAN SELATAN - Toto Supartono; Iing Nasihin; Feizal Tawaqal (Fakultas Kehutanan Universitas Winaya Mukti, 2019)
The polulation of Cat Family (Felidae) in Southeast Asia has declined in nature owing to its lost habitat, fragmentation one and massive hunting. Meanwhile, the research of Asiatic Golden Cats, Sunda Clouded Leopards, Marbled Cats, and Asian Leopard Cats is not much conducted. This research aimed to find out their distribution and habitat use in Southern Bukit Barisan National Park (BBSNP). The data intake employed Camera Trap, then analyzed by occupancy model with single season and single species applying R-software. It was found that Asiatic Golden Cat Occupancy Model yielded 0.75 in Intensive Protection Zone or Zona Perlindungan Intensive (IPZ) and 0.4 occupancy value in northen parts of Sourthern Bukit Barisan National Park (BBSNP). Furthermore, its Sunda Clouded Leopards resulted in 0.50 in IPZ and 0.42 occupancy value in northen parts of BBSNP. Its Asian Leopard Cats was 0.16 occupancy value in IPZ and unexecuted occupancy model in northen parts of BBSNP due to extremly low detection.